Suppressing the backward motion of a stick–slip piezoelectric actuator by means of the sequential control method (SCM). (September 2020) - Tang, Jinyan; Fan, Haoyin; Liu, Jiahui; Huang, Hu
Graphical abstract: Highlights: A sequential control method (SCM) was proposed to suppress the backward motion in stick–slip piezoelectric actuators. A piezoelectric actuator with two layers of structures (DFH and LFH) was developed. Feasibility of the SCM was theoretically analyzed by the finite element method. Ideal stepping displacement could be achieved when working under the SCM. Abstract: For stick–slip piezoelectric actuators working under the friction-inertia principle, the backward motion is nearly unavoidable especially at low driving frequency, which is detrimental to their driving performances. Accordingly, to suppress the backward motion of stick–slip piezoelectric actuators, this paper proposed a novel sequential control method (SCM). To verify the feasibility of SCM, an actuator prototype was designed and fabricated accordingly, and its output performances were tested experimentally. In this prototype, two flexure hinges and piezoelectric stacks were employed for driving and lifting, respectively. Before the generation of backward motion, the whole driving flexure hinge can be lifted up to separate from the mover by the lifting flexure hinge. Comparative experiments of the actuator working under the SCM and traditional stick–slip principle showed that backward motion could be significantly suppressed under the SCM, and the output displacement curve showed good stepping characteristics, proving the effectiveness of the proposed SCM.